Hematocrit, T3 and Metabolic Rate data - Elliott, Kyle H.; Hare, James F.; Le Vaillant, Maryline; Gaston, Anthony J.; Ropert-Coudert, Yan; Anderson, W. Gary (Dryad Digital Repository, 2014)
Excel spreadsheet with two tabs: one with hematocrit data and the other with T3/metabolic rate data. Headers are provided for each column.